1982
DOI: 10.1111/j.1365-2265.1982.tb00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Cushing's Syndrome in Pregnancy—treatment With Metyrapone

Abstract: A 23-year-old female presented with severe Cushing's syndrome in the 23rd week of pregnancy. Investigations showed plasma cortisol 770 nmol/l (08.00 h) and 850 nmol/l (23.00 h); plasma ACTH was 10 ng/l (08.00 h) and 27 ng/l (23.00 h); urinary free cortisol excretion was 2460 nmol/24 h. Dexamethasone 2 mg 6-hourly for 48 h suppressed the 08.00 h plasma cortisol only to 680 nmol/l. Abdominal C.T. scan showed a right adrenal adenoma. The patient was treated with metyrapone and a good clinical improvement ensued. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(32 citation statements)
references
References 33 publications
0
31
0
1
Order By: Relevance
“…Surgery is the preferred option, when it is safe during pregnancy or following delivery, while medical therapy is used to control hypercortisolism until surgery can be performed. Untreated maternal hypercortisolaemia has significant implications on maternal and foetal health and there is evidence that treatment improves the rate of live births (122,126). There are no approved medical treatments for use in pregnancy; however, there are several reports of the use of metyrapone or KTZ in this difficult clinical scenario.…”
Section: Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery is the preferred option, when it is safe during pregnancy or following delivery, while medical therapy is used to control hypercortisolism until surgery can be performed. Untreated maternal hypercortisolaemia has significant implications on maternal and foetal health and there is evidence that treatment improves the rate of live births (122,126). There are no approved medical treatments for use in pregnancy; however, there are several reports of the use of metyrapone or KTZ in this difficult clinical scenario.…”
Section: Pregnancymentioning
confidence: 99%
“…There are concerns that metyrapone may affect the biosynthesis of steroids in the placenta; however, several case reports describe its use in the first (127,128,129), second (123,127,129,130,131,132) and third trimesters (123,126,129,130,133,134). Metyrapone is generally well tolerated and doses up to 3 g have been used to control hypercortisolaemia (123,130).…”
Section: Pregnancymentioning
confidence: 99%
“…If the aetiology is adrenal adenoma, the therapeutic alternatives are unilateral adrenalectomy during pregnancy [10][11][12][13][14][15][16][17][18][19] Gormley et al [20] in 1982. Metyrapone, an inhibitor of 11ß-hydroxylase, leads to a reduction of cortisol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-four patients with 37 pregnancies in the period between 1961 and 1996, including our case, were identified. Unilateral adrenalectomy was performed during pregnancy in 12 of these patients [10][11][12][13][14][15][16][17][18][19] (group I), non-surgical or conservative management was adopted in the remaining 25 pregnancies [15,20,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] (group II) and all patients in group II received post partum adrenalectomy. Tables 1 and 2 compare the perinatal and maternal outcomes in group I and group II patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ketoconazole has been used in CS during pregnancy without untoward effects (28, 81,[96][97][98]. Although metyrapone may cause adrenal insufficiency in the neonate, it has been used during pregnancy but not always with symptom control (99)(100)(101)(102)(103)(104). Lindsay et al reported 20 women receiving medical therapy (11 patients metyrapone; 3, ketoconazole; 3, cyproheptadine; 1, aminoglutethimide; and 2, mitotane) for CS usually starting in the second or third trimester (28).…”
Section: Treatment Of Cushing's Disease During Pregnancymentioning
confidence: 99%